Iron Oxide Nanoparticles: Innovative Tool in Cancer Diagnosis and Therapy - Martinkova, Pavla; Brtnicky, Martin; Kynicky, Jindrich; Pohanka, Miroslav (Advanced healthcare materials, 2018)
Although cancer is one of the most dangerous and the second most lethal disease in the world, current therapy including surgery, chemotherapy, radiotherapy, etc., is highly insufficient not in the view of therapy success rate or the amount of side effects. Accordingly, procedures with better outcomes are highly desirable. Iron oxide nanoparticles (IONPs) present an innovative tool-ideal for innovation and implementation into practice. This review is focused on summarizing some well-known facts about pharmacokinetics, toxicity, and the types of IONPs, and furthermore, provides a survey of their use in cancer diagnosis and therapy.
Keywords: Neoplasms; nádory; Animals; železité sloučeniny; lidé; zvířata; magnetické nanočástice; Magnetite Nanoparticles; Ferric Compounds; Humans